A Lapsus, My Little Readers: The Presence of Psychoanalysis in Giorgio Manganelli's Pinocchio: Un libro parallelo. (2nd January 2019) - Diazzi, Alessandra
ABSTRACT: This article demonstrates the considerable influence of both psychoanalysis and analytical psychology on Giorgio Manganelli's rewriting of Carlo Collodi's Le avventure di Pinocchio in his Pinocchio: Un libro parallelo (1977), an aspect of this text that scholarship has mostly overlooked. Here, I examine this book in relation to the contemporary debate around psychoanalysis and the legitimacy of its dissemination in Italian culture. Specifically, I argue that Manganelli's 'parallel Pinocchio' can be interpreted as an oblique and ironic alternative to the polemical approach to psychoanalysis proposed by Sebastiano Timpanaro in Il lapsus freudiano (1974).